The functional status, rehospitalization, and hospital cost reduction in geriatric patients after the implementation of the universal health coverage program in the national referral hospital Indonesia (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Universal health coverage program (UHCP) might implicate negatively toward geriatric care with its impact on higher cost. The evaluation had to be made, especially in functional status, rehospitalization, and cost-effectiveness. METHODS Retrospective cohort study with historical control was done. Seventy two geriatric inpatients in the pre-UHCP group and 86 in the UHCP group were recruited from Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Subjects with geriatric syndromes admitted from July to December 2013 (pre-UHCP era) and January to June 2014 (UHCP era). Functional status changes, rehospitalization, and process indicators were observed. Cost reduction was calculated using the incremental cost-effectiveness ratio (ICER), whereby costs, functional status changes, and rehospitalization of both groups were used to identify the differences. RESULTS Proportions of functional status increase were 35.3% and 34.8% in the pre- UHCP and UHCP groups, respectively (p = 1.00) and the decrease were 5.9% and 4.5% in the pre-UHCP and UHCP group, respectively (p = 1.00). Rehospitalization rates were 21.7% and 18.1% (p = 0.603) in the pre-UHCP and UHCP groups, respectively. Mean hospital expenses were between 17.1 million IDR (1,221 USD; 1 USD = 14,000 IDR) for the pre-UHCP group and 20.8 million IDR (1,486 USD) for the UHCP group. ICER showed that hospitalization cost was 3.7 million IDR (264 USD) higher to increase 1 activity of daily living score in the UHCP era. As for rehospitalization, the cost was 600,000 IDR (43 USD) less, with 3.6% smaller in readmission. CONCLUSIONS There was no changes in patientsâ functional status after the UHCP implementation. There was a reduction in rehospitalization with lower cost in the UHCP era.